Increasing Teacher`s Organizational Commitment Through Strengthening Teamwork, Situational Leadership and Self-Efficacy - Koswara, Dudung; Hardhienata, Soewarto; Retnowati, Rita (AGUSPATI Research Institute, 2021)
Teachers’ commitment towards organization is important to be improved. Strengthening teamworks, good situational leadership by the principal and strong self-efficacy can be used as an effort to improve teachers’ commitment towards their organization. This study is aimed to determine the commitment of private Senior High School teachers in Sukabumi towards their organization through the study of relationship strength between research variable, teamworks, Principal’s situational leadership and self-efficacy. The research used correlational analysis and quantitative method while data collection techniques are collected through questionnaires. The population used in this research are 240 private permanent school teachers in Sukabumi. The sample of the research are 150 teachers calculated by Taro Yamane formula with a significance level of 0,05.Based on the results analysis, there is positive and significant relationship between Teamworks and Teachers’ commitment towards organization with the correlational coefficient ry.1 = 0,0346. There is positive and significant relationship between Principal’s situational leadership and teacher’s commitment towards organization with correlational coefficient ry.2 = 0,465 and there is positive and significant self-efficacy and teachers’ commitment towards organization with correlational coefficient ry.3 = 0,319. The conclusion based on STOREM analysis shows that all teamworks indicators influence teachers’ commitment towards their organization. It means, the stronger the teamworks, the higher commitment teachers have to their organization. All indicators of Principal’s situational leadership influence teachers’ commitment towards their organizations. It means, the stronger Principal’s situational leadership, the higher commitment teachers have to the organization. All indicators of self-efficacy influence teacher’s commitment towards organizations. It means, the stronger self-efficacy; the higher commitment teachers have to the organization.